PERUBAHAN BUDAYA JUAL BELI TRADISIONAL MENJADI JUAL BELI ONLINE (STUDI KASUS PENJUALAN ONLINE PADA TOKOBAGUS.COM) - Fathur Rohman (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2012)
Increasing economic growth is felt by most of society and government. It can be easily seen from the volume of trade balance higher each year. Even the very significant growth. The impact of economic growth is also felt by the people both small businesses and middle-class entrepreneurs. The more varied the level of consumerism has also increased business opportunities. This makes the higher trade competition. Things that piecemeal change the paradigm of most people to change the way the sale of the traditional way of buying and selling a conventional sale online by means of internet and websites that provide online trading services. Computer technology advances and internet that brought big changes. Thought transasksi simple market should be converted into a global sales, both locally, nationally and internationally. Between sellers with buyers can be met easily without face-to-face and without the clock. Transactions can be done anytime. Such sale and purchase transactions that occurred in Tokobagus.Com Keywords: buying and selling, traditional, Online, Tokobagus